2024
DOI: 10.3390/buildings14010270
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Performance of Hybrid Fibre Reinforced Magnesium Oxychloride Cement-Based Composites at Ambient and Elevated Temperature

Sanket Rawat,
Paul Saliba,
Peter Charles Estephan
et al.

Abstract: Magnesium oxychloride cement (MOC) is often recognized as an eco-friendly cement and has found widespread application in various sectors. However, research on its resistance against elevated temperatures including fire is very limited. This paper thoroughly investigated the mechanical performance of fibre reinforced MOC-based cementitious composite (FRMOCC) at ambient and elevated temperatures. A recently developed water-resistant MOC was used as the base matrix which was further reinforced using hybrid basalt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In general, the literature regarding FRMOC containing 2% PE fiber showed a significant improvement in the ductility of the composites (as shown in Figure 4) with out compromising the overall mechanical performance. In a recent investigation by Rawat et al [35], the influence of 2% basalt fiber on the mechanical properties of MOC was explored, revealing enhancements in compressive and tensile strengths alongside a notable reduction in strain capacity. In a subsequent study aiming to optimize both tensile strength and strain capacity, Ahmad et al [1] delved into the effects of hybrid fibers, specifically PE fiber and basalt fiber, on MOC behavior.…”
Section: Recent Developments In Frmoc-based Compositesmentioning
confidence: 99%
See 3 more Smart Citations
“…In general, the literature regarding FRMOC containing 2% PE fiber showed a significant improvement in the ductility of the composites (as shown in Figure 4) with out compromising the overall mechanical performance. In a recent investigation by Rawat et al [35], the influence of 2% basalt fiber on the mechanical properties of MOC was explored, revealing enhancements in compressive and tensile strengths alongside a notable reduction in strain capacity. In a subsequent study aiming to optimize both tensile strength and strain capacity, Ahmad et al [1] delved into the effects of hybrid fibers, specifically PE fiber and basalt fiber, on MOC behavior.…”
Section: Recent Developments In Frmoc-based Compositesmentioning
confidence: 99%
“…In a subsequent study aiming to optimize both tensile strength and strain capacity, Ahmad et al [1] delved into the effects of hybrid fibers, specifically PE fiber and basalt fiber, on MOC behavior. They observed that all FRMOC composites exhibited strain hardening behavior, with those containing 2% PE fiber demonstrating the highest tensile strength (10.95 MPa) and strain capacity (4.41%), potentially attributed to multiple cracking mechanisms illustrated in In a recent investigation by Rawat et al [35], the influence of 2% basalt fiber on the mechanical properties of MOC was explored, revealing enhancements in compressive and tensile strengths alongside a notable reduction in strain capacity. In a subsequent study aiming to optimize both tensile strength and strain capacity, Ahmad et al [1] delved into the effects of hybrid fibers, specifically PE fiber and basalt fiber, on MOC behavior.…”
Section: Recent Developments In Frmoc-based Compositesmentioning
confidence: 99%
See 2 more Smart Citations